Education on the impact of reverse osmosis (ro) drinking water toward health in village pb Selayang II Medan - Silalahi, Jansen; Sinaga, Siti Morin; Ginting, Nahitma; Rahman, Fathur (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
At this time, there is a lot of ready-to-drink drinking water consisting of mineral water and demineralized drinking water such as Reverse Osmosis (RO) both in packets and refills. Drinking water must meet biological, chemical, and physical requirements so that it does not have negative effects on health. One of the chemical requirements is about the main mineral content of calcium and magnesium in drinking water. Based on research results, drinking water with low minerals (usually expressed as low water hardness) if consumed for a long time will cause health problems, for example increasing the risk of several diseases such as cancer, coronary heart disease, and others. Absorption of toxic metals such as Pb will occur if the minerals calcium and magnesium are very low in drinking water. So, if there is a small amount of Pb toxic metals in food, it will be easily absorbed by the body when calcium and magnesium levels are low in drinking water. However, if calcium and magnesium are sufficient in drinking water, the absorption of Pb, both in drinking water and other food, will be inhibited or not occur. Means can avoid diseases caused by these toxic metals. Therefore, the World Health Organization (WHO) determined that the calcium and magnesium content in drinking water each with a minimum requirement is 20 mg of calcium and 10 mg of magnesium in one liter of drinking water. The Indonesian Ministry of Health in 1975 only stated that the maximum calcium content in drinking water was 75 mg / liter of drinking water and there were no minimum requirements. Then the Ministry of Health in 2010 did not include the calcium and magnesium requirements but only the hardness requirements. So low-mineral drinking water will absorb (trap) the minerals present in other foods and dispose of them so that the body lacks minerals in the long run. Water without minerals will also reduce the process of absorption of minerals in digestion, and can even bind minerals from the body if consumed without other food. Low mineral water is not good as drinking water, especially demineralized drinking water that does not contain minerals can cause health problems especially water without minerals such as RO drinking water. The results showed that the levels of calcium (Ca) and magnesium (Mg) in bottled and refilled drinking water in Medan more did not reach the minimum levels of calcium and magnesium, meaning that drinking water was low in minerals. Even more important is that producers of refilled RO drinking water are in Medan (some claim to get permission from the government) and there is even a bottled RO drinking water product which means getting permission from the Drug and Food Control (POM).